Bariatric surgery – time to replace with GLP-1?. (3rd July 2017) - Webb, Dominic-Luc; Abrahamsson, Niclas; Sundbom, Magnus; Hellström, Per M.
Abstract: Obesity with a body mass index (BMI) over 30 kg/m 2 represents a significant risk for increased morbidity and mortality, with reduced life expectancy of about 10 years. Until now, surgical treatment has been the only effective longterm intervention. The currently standardized method of bariatric surgery, gastric bypass, means that many gastrointestinal peptide hormones are activated, yielding net reductions in appetite and food intake. Among the most important gut peptide hormones in this perspective is glucagon-like peptide-1 (GLP-1), which rises sharply after gastric bypass. Consistent with outcomes of this surgery, GLP-1 suppresses appetite and reduces food intake. This implies that GLP-1 has the potential to achieve a similar therapeutic outcome as gastric bypass. GLP-1 analogs, which are used for the treatment of type 2 diabetes mellitus, also lead to significant weight loss. Altered hormonal profiles after gastric bypass therefore indicate a logical connection between gut peptide hormone levels, weight loss and glucose homeostasis. Furthermore, combinations of GLP-1 with other gut hormones such as peptide YY (PYY) and cholecystokinin (CCK) may be able to reinforce GLP-1 driven reduction in appetite and food intake. Pharmacological intenvention in obesity by use of GLP-1 analogs (exenatide, liraglutide, albiglutide, dulaglutide, lixisenatide, taspoglutide) and inhibitors of dipeptidyl peptidase-IV (DPP-IV) degradation that inactivate GLP-1 (sitagliptin, vildagliptin), leading to reduced appetite and weight with positive effects on metabolic control, are realistically achievable. This may be regarded as a low-risk therapeutic alternative to surgery for reducing obesity-related risk factors in the obese with lower BMIs.